Flood risk science and management - Faulkner, Hazel; Pender, Gareth (Wiley-Blackwell, 2011)
"Acceptance of the reality of climate change has introduced a further shift in flood studies and the management of flood risk. Until recently, assessment of flood hazards depended on statistical manipulation of historical records and the current pattern of land-use and economic activity in the area at risk. It is now accepted that future flood risks cannot be estimated from historical flood probabilities or current socio-economic conditions. Consequently, new approaches to flood management must rely on climate change predictions and scenarios for socio-economic change that are highly uncertain. The requirement to place the treatment of uncertainty at the heart of flood risk management places further demands on the scientists and engineers responsible for designing and delivering science and technologies capable of avoiding unacceptable increases in flood risk during the remainder of the 21st century. Conversely, the benefits of flooding to aquatic, riparian, floodplain and, particularly, wetland environments and ecosystems are being increasingly recognised. In this context, climate change impacts involving reductions in flood frequency and duration threaten many of the world's most bioproductive and diverse ecosystems, and steps to promote managed flooding become vital to conserving endangered species and their habitats. A successful flood risk management strategy will therefore minimise the adverse impacts of flooding while, at the same time, allowing for uncertainties and maximising the environmental benefits. The Flood Management Handbook provides a comprehensive state-of-the-art summary of current international research and practice in each of the following key components of flood risk management"